Influence of students' motivation on academic performance among non-food science students taking food science course - Sukor, Rashidah; Mohd Ayub, Ahmad Fauzi; Zawawi, Norhasnida; Mahmud @ Ab Rashid, Nor Khaizura (Human Resource Management Academic Research Society, 2017)
The purpose of this study was to investigate motivation towards food science course among non-food science students. Six factors of students’ motivation, i.e., self-efficacy, active learning strategies, science learning value, performance goal, achievement goal and learning environment stimulation were investigated to predict factors that influence their academic achievement towards food science course. The sample of the study consisted of 84 undergraduate non-food science students from various faculties at a local public university. The data were adapted from Students’ Motivation Toward Science Learning (SMTSL) questionnaire and was validated as a reliable tool. The results of the data analysis revealed that students had a moderate level of motivation towards food science course. A positive significant relationship score was obtained between overall motivations with academic performance. Three sub-factors, i.e., self-efficacy, active learning strategies and achievement goal were found to have positive significant relationship with academic performance. Multiple regression analysis indicated that self-efficacy and achievement goal had a positive contribution to the study.